ETORICOXIB VERSUS PIROXICAM IN ACCENTUATING THE COGNITIVE FUNCTIONS - Rafi Abdul-Majeed Al-Razzuqi; Wesal Sami Mehasin; Ali Husain Hasan (Scholar Express Journals, 2023)
Cognitive functions are processes of knowing. When it is impaired, reviving is needed. Studies to bustle off the psychomotor activities using COX-1 inhibitors revealed variable results. Aim: To evaluate the effects of a single oral dose of etoricoxib and piroxicam (COX-2 inhibitors) on cognitive activity in healthy, young volunteers. Subjects and Methods: Thirty-two healthy young volunteers were participated, allocated into two groups. After a7-day washed-out period, each participant was randomly given a single oral dose of either etoricoxib (90mg) or piroxicam (10mg) or placebo. Psychomotor tests were performed to record their sensory and motor reactions. Results: the placebo-administered subjects had non-significant changes in both choice reaction time and critical flicker fusion. Etoricoxib-administered subjects had a significantly reduced recognition reaction time without a significant effect on motor reaction time. While piroxicam-administered ones had a significant reduction in motor reaction time without a significant effect on recognition reaction time. All drug-given individuals had a non-significant change in choice reaction time when compared with corresponding baseline and placebo values.
Keywords: Etoricoxib; choice reaction time; critical flicker fusion; piroxicam